EP291 Surgery for early cervical cancer: a 10-year retrospective outcome comparison between laparoscopic and open radical hysterectomy in an irish centre. (1st November 2019) - Fullston, E; Abu Saadeh, F; Gleeson, N; Thompson, C
Abstract : Introduction/Background: Following publication of the LACC trial, laparoscopic radical hysterectomy for the treatment of cervical cancer is now debated. We aimed to measure outcomes in our own population.This review aims to compare overall survival and risk of recurrence among women who underwent open versus laparoscopic radical hysterectomy for early cervical cancer at the largest provider of gynaecological cancer care in the Republic of Ireland over 10 years. Methodology: All cases of cervical cancer diagnosed from January 2005 until January 2016 were reviewed. Patient characteristics, disease stage, histology, node status, method of treatment including surgery, adjuvant radiation or chemotherapy were recorded. Intervals to death and/or recurrence were calculated. Inclusion criteria were: Stage 1A1, 1A2 or 1B1 adenocarcinoma, squamous cell or adenosquamous carcinoma of the cervix without node involvement; radical hysterectomy (open or laparoscopic). Results: Of 608 new cases of cervical cancer, 476 were excluded (not treated surgically [n=392]; treated with surgery other than RH [n=18]; histology other than SCC/AC/ASC [n=14]; stage beyond IB1 [n=26]; node positive histology [n=11]; death but no recurrence [n=4]; lost to follow-up [n=11]). For the laparoscopic (n=54) and open (n=78) RH groups respectively, baseline characteristics were similar: mean age at diagnosis was 38.2 vs 43.9 years, histology was SCC in 64.8% vs 66.7%, adenocarcinoma in 7.4% vs 5.1% and adenosquamous in 29.6% vs 28.2%. Death occurred in 13.0% (n=7/54) vs 6.4% (n=5/78) [p=0.19]; recurrence was diagnosed in 13.0% (7/54) vs 9.0% (n=7/78) [P=0.46]. Conclusion: Our findings showed no statistical significance between open versus laparoscopic surgery in terms of recurrence rates and overall survival. However, numerically there were more deaths within the laparoscopic group. A further sub-analysis will be conducted on tumour volume, multimodal treatment with regards to risk of recurrence. Disclosure: Nothing to disclose.